PENDAMPINGAN PEMBUATAN HANDSOAP BERBAHAN DASAR DAUN SIRIH SEBAGAI STRATEGI PENANGANAN COVID-19 - Tsalitsatul Maulidah; Ayu Rahmawati (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2021)
The aim of this assistance is to instill insights from an early age in junior high school children about the importance of washing hands for the prevention of Covid-19 in Dadapan village. Apart from seeing the implications of this socialization for public health, this activity is expected to be able to create small businesses to improve the economy of the people of Dadapan Solokuro village through the development of making handsoap with local raw materials that are easily available. The method in this mentoring is by using socialization. The steps in this mentoring use three stages, namely the preparation stage, the implementation stage, and the final stage. The results obtained were that before the assistance was carried out, most of the students at Nurul Fattah Integrated Junior High School did not know how to make handsoap from natural ingredients. After the socialization was carried out on how to make handsoap students of SMP Integrated Nurul Fattah, there was an increase in knowledge and skills in making handsoaps from natural materials. According to the results of the survey conducted, students already understand very well how to prevent and avoid Covid-19 seen from a percentage of 100%.